Implementation of a fuzzy-based level control using SCADA - Aydogmus, Zafer (Pergamon-Elsevier Science Ltd, 2009)
This paper presents a SCADA (supervisory control and data acquisition) control via PLC (programmable logic controller) for a fluid level control system with fuzzy controller. For this purpose, a liquid level control set and PLC have been assembled together. The PLC used in this work has no fuzzy module or software. The required fuzzy program algorithms are written by the author. Sugeno type fuzzy algorithm has been used in this study. To achieve the parameters of the membership functions, MATLAB/Simulink program has been used. PLC has been programmed using achieved fuzzy algorithm. A SCADA system has been composed for monitoring of water level in tank and position of the actuator valve. The main objective of this work is to present an implementation setup has been realized with no fuzzy logic controller module/software in this study. The system described in this paper is a low cost solution that is intended for control purposes. Simulation and implementation results have been compared and similar results obtained with a good degree of accuracy. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Fuzzy logic; Programmable logic controller; Level control; SCADA